(untitled) (Ágora Journal, 2024)
Our aim is to debate the systemic oppression of dissident bodies propagated in the music of whiteness in Fortaleza’s Belle Époque. First and foremost, we understand the Belle Époque as a discourse that operates within the logic of coloniality, imposing a pattern of domination developed by modernity. This pattern affects the reality of bodies placed in dissent in relation to power structures and whiteness as a raciality historically constructed as a fiction of superiority that materially and symbolically benefits white people. The documents analyzed are songs recorded on sheet music and 78 rpm records, as well as correspondence, music books and periodicals. We reflect on these issues based on the reading of authors from the Decolonial Turn, Post-Colonial Studies and Intersectional Feminisms.